2013
DOI: 10.1080/19359705.2013.834858
|View full text |Cite
|
Sign up to set email alerts
|

Depression and HIV Risk Taking Among Men Who Have Sex with Other Men and Who Use the Internet to Find Partners for Unprotected Sex

Abstract: PURPOSE This study examines the prevalence of depression in a sample of MSM who are at high risk for HIV. It examines the relationship between depressive symptomatology and involvement in HIV risk behaviors, and the factors associated with greater depressive symptomatology. METHODS The data come from a national random sample of 332 MSM who used any of 16 websites to identify men with whom they could engage in unprotected sex. Data were collected via telephone interviews. RESULTS Depression was more prevale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 76 publications
0
13
2
Order By: Relevance
“…Klein [33] found that depression, while not related to actual sexual risk behaviors among gay and bisexual men, was associated with condom use beliefs which were, in turn, related to sexual risk behavior. Perdue et al [34] found that depression was linked with increased number of partners among MSM but not with increased sexual risk-taking with those partners.…”
Section: Introductionmentioning
confidence: 99%
“…Klein [33] found that depression, while not related to actual sexual risk behaviors among gay and bisexual men, was associated with condom use beliefs which were, in turn, related to sexual risk behavior. Perdue et al [34] found that depression was linked with increased number of partners among MSM but not with increased sexual risk-taking with those partners.…”
Section: Introductionmentioning
confidence: 99%
“…Previous international research underscores that homosexuality-related stigma and discrimination are associated with a higher risk of depression (16, 17). Depression has been found to be highly prevalent among MSM, particularly HIV-positive men (18, 19), and is considered a major health issue among MSM (20). Furthermore, homosexuality-related stigma, discrimination, and depression have been found to be associated with engaging in HIV-related risky behaviors such as CAI (2123), drug use (24, 25), having sex while on drugs (26), less awareness and underutilization of HIV prevention services (2729), and experiencing less benefit from participating in HIV prevention interventions (27).…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have found higher rates of psychological problems in individuals who use the internet to seek social interactions or meet romantic partners, including higher levels of social anxiety, depression, and loneliness, as well as lower self-esteem (Caplan, 2007;Kim, Kwon, & Lee, 2009;Klein, 2014;Morrison & Gore, 2010). Given that many transgender men and women face discrimination and consequently have relatively high rates of psychiatric symptoms, examination of mental health among transgender individuals who meet partners online is warranted.…”
Section: Sexuality and The Internetmentioning
confidence: 96%